The job search : - Zarna, Barbara (McGraw-Hill, 1997)
This text provides step-by-step guidance for creating the necessary documents to find a job. In addition to helping stu-dents land their first job, the text also provides students information on the importance of staying flexible and marketable throughout their working lives.